Electrochemical sensor based on Co3O4-coated MXene-rGO composite material and preparation method and application thereof
By modifying the electrodes with Co3O4@MXene-rGO composite, the problem of low sensitivity and susceptibility to interference in dopamine detection is solved, efficient and quantitative dopamine detection is achieved, and the reproducibility and stability of the detection is improved.
Patent Information
- Application Number
- CN202411688544.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-03-25
AI Technical Summary
Existing electrochemical sensors have low sensitivity, are susceptible to interference, have poor reproducibility and stability in dopamine detection.
The electrode was modified with Co3O4@MXene-rGO composite material, and the Co3O4@MXene-rGO nanocomposite was prepared by ultrasonic, centrifugation, washing, and drying, and used to construct electrochemical sensors.
It realizes efficient and quantitative detection of dopamine, has strong selectivity and anti-interference ability, and has good reproducibility and stability.
Smart Images

Figure CN119688804A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of electrochemical sensors, and in particular to an electrochemical sensor based on a Co3O4@MXene-rGO composite material, and a preparation method and application thereof. Background Art
[0002] Dopamine (DA) is an important monoamine neurotransmitter that plays a vital role in human metabolism, central nervous system, cardiovascular, renal, endocrine, respiratory and hormonal systems. The dopamine concentration in a healthy human body needs to be maintained within the normal range. Too high a concentration may lead to diseases such as hypertension and heart failure, while too low a concentration is associated with diseases such as depression, Parkinson's disease and Alzheimer's disease. Therefore, dopamine concentration can be used as an effective marker for central nervous system diseases. Sensitive and accurate detection of dopamine concentration is of great significance for medical diagnosis and pathological research. At present, the methods used to determine dopamine concentration are mainly instrumental detection methods, such as gas chromatography-mass spectrometry, high performance liquid chromatography, surface enhanced Raman spectroscopy, surface plasmon resonance spectroscopy, fluorescence spectrophotometry, capillary electrophoresis, etc. Although the above technologies have high selectivity and sensitivity, they still have disadvantages such as complex sample pretreatment, high instrument cost and long analysis time. Since dopamine is electrochemically active, electrochemical sensing has become an ideal method for detecting dopamine due to its low cost, high sensitivity, simple operation, and strong real-time monitoring capabilities. Accordingly, the design and synthesis of high-performance nanomaterial-modified electrodes have become the key to constructing ultra-sensitive electrochemical sensors for detecting dopamine.
[0003] Patent publication number CN118191061A discloses a dopamine detection electrochemical sensor based on nanoporous MXene materials, which includes: a nanoporous MXene electrode as a working electrode, a Pt electrode as a counter electrode, and an Ag / AgCl electrode as a reference electrode. The nanoporous MXene electrode has a large specific surface area and abundant active sites, thereby enhancing dopamine adsorption, so that the electrochemical detection of dopamine has a lower detection limit and a wider linear range. However, the preparation steps of the nanoporous MXene electrode in the electrochemical sensor are: adding H2O2 solution to the MXene solution to prepare the nanoporous MXene material; adding Nafion solution to the nanoporous MXene material solution, modifying the mixed solution to the glassy carbon surface, and preparing the nanoporous MXene electrode. Summary of the invention
[0004] The purpose of the present invention is to overcome the defects of the above-mentioned prior art such as low sensitivity, susceptibility to interference from other substances, poor detection reproducibility and stability, and to provide an electrochemical sensor based on Co3O4@MXene-rGO composite material and its preparation method and application, which is used for efficient and quantitative detection of dopamine, has strong selectivity for dopamine, strong anti-interference ability, and good reproducibility and stability.
[0005] The purpose of the present invention can be achieved by the following technical solutions:
[0006] One of the technical solutions of the present invention is to provide an electrochemical sensor based on Co3O4@MXene-rGO composite material, wherein the electrochemical sensor comprises a working electrode, a counter electrode and a reference electrode, and the surface of the working electrode is modified with Co3O4@MXene-rGO nanocomposite material. The electrochemical sensor has a large electrochemically active surface area and excellent electrical conductivity.
[0007] Furthermore, the Co3O4@MXene-rGO nanocomposite material includes Co3O4 nanoparticles and MXene-rGO composite aerogel, and the Co3O4 nanoparticles are uniformly distributed on the surface of the three-dimensional MXene-rGO composite aerogel.
[0008] Furthermore, the preparation method of the Co3O4@MXene-rGO nanocomposite material is as follows: Co3O4 nanoparticles are mixed with MXene-rGO composite aerogel, and the Co3O4@MXene-rGO nanocomposite material is obtained by ultrasonication, centrifugation, washing, and drying. The prepared Co3O4@MXene-rGO nanocomposite material has a uniformly dispersed perfect morphology.
[0009] Furthermore, the mass ratio of the Co3O4 nanoparticles to the MXene-rGO composite aerogel is 1 to 3:1, preferably 2:1.
[0010] Furthermore, the preparation process of the Co3O4 is as follows: a cobalt source and 2-methylimidazole are dissolved in methanol respectively, a cobalt-based MOF is obtained by mixing, reacting, centrifuging, and drying, and the Co3O4 nanoparticles are obtained by calcining;
[0011] The preparation process of the MXene-rGO composite aerogel is as follows: MXene and rGO are ultrasonically treated and then freeze-dried to obtain the MXene-rGO composite aerogel.
[0012] More preferably, in the process of preparing the Co3O4 nanoparticles:
[0013] The molar ratio of the cobalt source to 2-methylimidazole is 1:4-12.
[0014] The cobalt source includes cobalt nitrate, cobalt chloride, and cobalt acetate.
[0015] The calcination temperature is preferably 350-450°C, and the calcination time is 2-6h, preferably 2-4h;
[0016] During the preparation of the MXene-rGO composite aerogel:
[0017] The mass ratio of MXene to rGO is 1:0.5-2.
[0018] The MXene includes Ti3C2 MXene, Ti2C MXene, Nb2C MXene, V2C MXene,
[0019] The reduced graphene oxide (rGO) is obtained by reducing a single layer of graphene oxide (GO);
[0020] The drying temperature is 40-80° C. and the drying time is 5-20 hours.
[0021] Furthermore, the MXene-rGO composite aerogel is a three-dimensional MXene-rGO composite aerogel.
[0022] More preferably, in the preparation process of the Co3O4 nanoparticles, a solid is obtained by centrifugation, and then the obtained solid is washed with water and ethanol for 1 to 5 times respectively.
[0023] Furthermore, the preparation process of the Ti3C2 MXene is: taking Ti3AlC2 as a precursor and obtaining Ti3C2 MXene by etching.
[0024] More preferably, the etching is chemical etching, the etching temperature is 30 to 60° C., preferably 40 to 50° C., and the etching time is 12 to 48 hours, preferably 20 to 30 hours.
[0025] More preferably, the preparation process of rGO is: taking GO as raw material and performing hydrothermal reduction to obtain rGO.
[0026] More preferably, the temperature of the hydrothermal reduction is 120 to 200° C., preferably 160 to 200° C., and the time of the hydrothermal reduction is 6 to 24 hours, preferably 8 to 16 hours.
[0027] More preferably, the reducing agent for the hydrothermal reduction comprises ascorbic acid, sodium borohydride, and hydrazine hydrate.
[0028] Furthermore, the working electrode is a glassy carbon electrode or a screen-printed electrode whose surface is modified with Co3O4@MXene-rGO nanocomposite material;
[0029] The counter electrode includes a platinum wire electrode, a platinum sheet electrode, and a graphite electrode;
[0030] The reference electrode includes an Ag / AgCl electrode and a calomel electrode.
[0031] Furthermore, the glassy carbon electrode needs to be pre-activated, and the glassy carbon electrode is polished to a mirror surface with aluminum oxide powder on a polishing flannel cloth, and then ultrasonically cleaned several times with pure water and ethanol respectively, and activated by cyclic voltammetry scanning in H2SO4 solution, and then washed to obtain an activated glassy carbon electrode.
[0032] The second technical solution of the present invention is to provide a method for preparing an electrochemical sensor based on Co3O4@MXene-rGO composite material, dispersing the Co3O4@MXene-rGO nanocomposite material in a solvent to obtain a Co3O4@MXene-rGO nanocomposite material suspension, dripping it on the surface of the working electrode, and after drying, assembling it with a reference electrode and a counter electrode to obtain an electrochemical sensor.
[0033] Furthermore, the drop coating amount of the Co3O4@MXene-rGO nanocomposite suspension is 10-150 μL / cm 2 , preferably 14 to 130 μL / cm 2 , more preferably 80 to 90 μL / cm 2 .
[0034] The concentration of the Co3O4@MXene-rGO nanocomposite in the Co3O4@MXene-rGO nanocomposite suspension is 1 to 5 mg / mL;
[0035] The solvent includes water and ethanol.
[0036] The third technical solution of the present invention is to provide an application of an electrochemical sensor based on Co3O4@MXene-rGO composite material for the detection of dopamine.
[0037] Furthermore, the electrochemical performance of the electrochemical sensor can be detected by cyclic voltammetry (CV), and the electrolyte is a buffer solution containing dopamine.
[0038] Furthermore, the electrochemical sensor is applied to the detection of dopamine, and the detection process includes the following steps:
[0039] (1) Optimizing the test conditions for detecting dopamine by the electrochemical sensor;
[0040] (2) Under the optimal experimental conditions, the DPV method was used to measure the oxidation peak current of dopamine, and a quantitative standard curve was established based on different oxidation peak currents and corresponding dopamine concentrations;
[0041] (3) Under the same experimental conditions, the dissolution peak current of the sample to be tested is measured, and then the dopamine content in the actual sample to be tested is calculated based on the dissolution peak current and the standard curve equation.
[0042] Furthermore, in step (1), the test conditions optimization include the drop amount of the Co3O4@MXene-rGO composite material suspension, the pH value of the buffer solution, and the scanning rate.
[0043] Furthermore, in step (1), the drop coating amount of the Co3O4@MXene-rGO composite material suspension under the test conditions is 10-150 μL / cm 2 , preferably 14 to 130 μL / cm 2 , more preferably 80 to 90 μL / cm 2 ; The concentration of the Co3O4@MXene-rGO nanocomposite in the Co3O4@MXene-rGO nanocomposite suspension is 1 to 5 mg / mL;
[0044] Furthermore, in step (1), the pH of the test condition buffer solution is 5 to 9, preferably 5 to 7, and more preferably 6.2;
[0045] Furthermore, in step (2), the DPV method is used to test the dopamine oxidation peak current, and the scanning potential is 0 to 0.4 V;
[0046] Furthermore, in step (2), the concentration of dopamine is 0.1 to 300 μM;
[0047] Furthermore, in step (3), the actual sample includes a sample containing dopamine such as a human serum sample, urine, and dopamine injection.
[0048] Compared with the prior art, the present invention has the following advantages:
[0049] (1) The present invention uses Co3O4@MXene-rGO composite material to construct an electrochemical sensor. Co3O4 is Co 2+ and Co 3+ The coexisting mixed-valence structure has excellent redox properties and outstanding electrocatalytic activity. The MXene-rGO composite aerogel has a large specific surface area and conductivity. The combination of the two can not only maintain their respective inherent properties, but also produce new synergistic effects, providing more reactive sites for dopamine and effectively improving the sensitivity of dopamine detection.
[0050] (2) The electrochemical sensor constructed by the present invention realizes efficient and quantitative detection of dopamine. In the concentration range of 0.1 to 300 μM, the oxidation peak current shows a good linear relationship with the dopamine concentration.
[0051] (3) The electrochemical sensor constructed by the present invention has strong selectivity for dopamine, has a small current response to interferences such as ascorbic acid, urea, glucose, glycine, proline and coexisting inorganic ions, and has good reproducibility and stability.
[0052] (4) Co3O4 is a transition metal oxide with a spinel crystal structure, which has rich redox properties and excellent electrocatalytic activity, but its inherent low conductivity and severe aggregation hinder its practical application. The present invention attaches Co3O4 to a high-surface-area three-dimensional MXene-rGO composite aerogel to prepare a composite material, which will effectively overcome this problem and make it a good electrocatalytic material.
[0053] (5) The present invention adopts the MOF derivatization method to obtain Co3O4 with perfect cubic morphology, and loads it on a three-dimensional MXene-rGO composite aerogel with high conductivity and large specific surface area, and prepares the Co3O4@MXene-rGO composite material by ultrasonic mixing. The composite material prepared by this method makes the active center Co3O4 uniformly dispersed, effectively improving the electrocatalytic activity of the material. BRIEF DESCRIPTION OF THE DRAWINGS
[0054] Figure 1 The morphological structure characterization diagrams of Co3O4, MXene, and Co3O4@MXene-rGO nanocomposites prepared in Example 1, a. SEM image of Co3O4, b. TEM image of MXene nanosheets, c. SEM image of Co3O4@MXene-rGO composite nanomaterials, d. HRTEM image of Co3O4@MXene-rGO composite nanomaterials;
[0055] Figure 2 XRD patterns of Co3O4 and its standard card (JCPDS NO.42-1467) and Co3O4@MXene-rGO nanocomposites;
[0056] Figure 3 Cyclic voltammetry curves of dopamine at different working electrodes;
[0057] Figure 4 This is a diagram showing the effect of different electrode material drop coating amounts on the electrochemical signal of the electrochemical sensor;
[0058] Figure 5The diagrams are the effects of different buffer solution pH on the electrochemical signals of the electrochemical sensor, a. The effect of buffer solution pH on the electrochemical signal, b. The relationship between the oxidation peak potential of dopamine on the working electrode and pH;
[0059] Figure 6 The diagrams are the effects of different scan rates on the electrochemical signals of the electrochemical sensor, a. The effect of scan rate on the electrochemical signal, b. The linear relationship between the oxidation peak current Ipa and the reduction peak current Ipc of dopamine and the scan rate;
[0060] Figure 7 The Co3O4@MXene-rGO / GCE has a dopamine concentration of 0.1 mol·L -1 ~300mol·L -1 a. Current response differential pulse voltammetry curve of the range, b. Linear relationship between dopamine concentration and current value. DETAILED DESCRIPTION
[0061] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. This embodiment is implemented based on the technical solution of the present invention, and a detailed implementation method and a specific operation process are given, but the protection scope of the present invention is not limited to the following embodiments. Based on the given embodiments, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.
[0062] Unless otherwise specified, the reagents, methods, instruments and equipment used in the present invention are conventional reagents, methods, instruments and equipment in the art.
[0063] In the following embodiments, the CAS number of Ti3AlC2 is 196506-01-1, 400 mesh, purchased from Jilin Yiyi Technology Co., Ltd.; the CAS number of ascorbic acid is 50-81-7, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.; GO purity: 98.5%, thickness 1NM, sheet diameter 0.2-10U, purchased from Jiangsu Xianfeng Nanomaterial Technology Co., Ltd.; the glassy carbon electrode is CHI104 type, the Ag / AgCl electrode is CHI111 type, and the platinum wire electrode is CHI115 type, all of which are purchased from Shanghai Chenhua Instrument Co., Ltd.
[0064] Example 1
[0065] An electrochemical sensor based on Co3O4@MXene-rGO composite material, the preparation process of which includes the following steps:
[0066] (1) Preparation of Co3O4 nanoparticles
[0067] Weigh 0.291g of Co(NO3)2·6H2O and add 20ml of methanol, stir magnetically for 10min to obtain liquid A; weigh 0.328g of 2-methylimidazole and add 20ml of methanol, stir magnetically to obtain liquid B. Then pour liquid B into liquid A to mix, stir continuously for 24 hours at room temperature, centrifuge and wash with methanol at 6000rpm for 3 times, centrifuge for 5min each time, and vacuum dry at 60℃ to obtain purple powder. The obtained purple powder is calcined at 400℃ for 2h in a muffle furnace, and cooled naturally to obtain black Co3O4 nanoparticles, which are derived from MOF.
[0068] (2) Preparation of MXene-rGO composite aerogel
[0069] Add 1.6g LiF to 20mL 9mol / L HCl solution and stir for 10 minutes to obtain an etching solution. Then gradually add 1g Ti3AlC2 powder to the above etching solution and stir at 45°C for 24 hours. Then wash the solid residue with deionized water and centrifuge several times until the pH value of the supernatant reaches 6. Collect the obtained solids and redisperse them, and sonicate them in an ice water bath and argon environment. Then centrifuge the dark green dispersion at 3000pm for 60min, collect the upper liquid and freeze-dry it to obtain MXene nanosheets, and store them for later use.
[0070] 100 mg GO was used as the raw material and 0.5 g ascorbic acid was used as the reducing agent. After ultrasonic homogenization to obtain a mixed solution, the mixed solution was transferred to a high-pressure reactor and reacted at 180 ° C for 12 hours in a homogeneous reactor. After cooling to room temperature, the solid was centrifuged at 5000 rpm for 5 minutes, washed with water and ethanol for 3 times respectively, and dried in a vacuum drying oven at 60 ° C overnight to obtain rGO. The prepared MXene and rGO were mixed in ultrapure water at a mass ratio of 1:1. After ultrasonic treatment for 30 minutes, the mixed solution was transferred to a freeze-drying container and quickly frozen for 72 hours to obtain a MXene-rGO composite aerogel.
[0071] (3) Preparation of Co3O4@MXene-rGO composites
[0072] The Co3O4 nanoparticles and MXene-rGO composite aerogel were fully mixed by stirring and ultrasound in a mass ratio of 2:1 to obtain a uniform solution. The mixed solution was centrifuged at 6000 rpm for 5 min, and the centrifuged solids were collected and dried in a vacuum drying oven at 60°C for 24 h to obtain the Co3O4@MXene-rGO nanocomposite material.
[0073] (4) Preparation of electrochemical sensors
[0074] The glassy carbon electrode (GCE) was polished to a mirror surface using 0.3 μm and 0.05 μm alumina powder on a polishing flannel, respectively, and ultrasonically cleaned several times with pure water and ethanol, respectively, and dried naturally. The GCE was activated using cyclic voltammetry (CV) in 0.5 mol / l H2SO4 solution with a scan rate of 0.1 V s -1 , the voltage range is -1 to 1V. After washing and drying, a clean and activated glassy carbon electrode is obtained and dried for later use.
[0075] 2.0 mg of Co3O4@MXene-rGO composite material was added to 1 ml of purified water and ultrasonicated to obtain a 2 mg / ml fully dispersed Co3O4@MXene-rGO composite material suspension. 5.0 μL of Co3O4@MXene-rGO composite material suspension was dropped on the pretreated GCE surface to make the drop coating amount of the Co3O4@MXene-rGO nanocomposite suspension 70.7 μL / cm 2 , and dried in an oven at 37 °C to obtain the modified electrode Co3O4@MXene-rGO / GCE, which was used as the working electrode.
[0076] The electrochemical sensor adopts a three-electrode system, with Co3O4@MXene-rGO / GCE as the working electrode, Ag / AgCl electrode as the reference electrode, and platinum wire electrode as the counter electrode. The electrochemical response of the electrochemical sensor to dopamine is detected by cyclic voltammetry. The electrolyte is a PBS buffer solution containing 150μmol / L dopamine, the concentration of the PBS buffer solution is 0.1mol / L, the pH is 6.2, the test potential range is 0V to 0.4V, and the scan rate is 100mV / s.
[0077] Example 2
[0078] Compared with Example 1, most of the details are the same, except that the mass ratio of Co3O4 nanoparticles and MXene-rGO composite aerogel is adjusted to 1:1.
[0079] Example 3
[0080] Compared with Example 1, most of the contents are the same, except that the mass ratio of Co3O4 nanoparticles and MXene-rGO composite aerogel is adjusted to 3:1.
[0081] Example 4
[0082] Compared with Example 1, most of the steps are the same, except for step (5) in the preparation of the electrochemical sensor:
[0083] 1.0 μL of Co3O4@MXene-rGO composite suspension was dropped on the pretreated GCE surface, so that the drop amount of the Co3O4@MXene-rGO nanocomposite suspension was 14.1 μL / cm 2 .
[0084] Example 5
[0085] Compared with Example 1, most of the steps are the same, except for step (5) in the preparation of the electrochemical sensor:
[0086] 3.0 μL of the Co3O4@MXene-rGO composite suspension was dropped onto the pretreated GCE surface so that the drop coating amount of the Co3O4@MXene-rGO nanocomposite suspension was 42.4 μL / cm 2 .
[0087] Example 6
[0088] Compared with Example 1, most of the steps are the same, except for step (5) in the preparation of the electrochemical sensor:
[0089] 7.0 μL of the Co3O4@MXene-rGO composite suspension was dropped onto the pretreated GCE surface, so that the drop coating amount of the Co3O4@MXene-rGO nanocomposite suspension was 99.0 μL / cm 2 .
[0090] Example 7
[0091] Compared with Example 1, most of the steps are the same, except for step (5) in the preparation of the electrochemical sensor:
[0092] 9.0 μL of the Co3O4@MXene-rGO composite suspension was dropped onto the pretreated GCE surface, so that the drop coating amount of the Co3O4@MXene-rGO nanocomposite suspension was 127.3 μL / cm 2 .
[0093] Example 8
[0094] Compared with Example 1, most of the steps are the same, except for step (5) in the preparation of the electrochemical sensor:
[0095] The electrolyte was a PBS buffer solution containing 150 μmol / L dopamine, with a pH of 5.2.
[0096] Example 9
[0097] Compared with Example 1, most of the steps are the same, except for step (5) in the preparation of the electrochemical sensor:
[0098] The electrolyte was a PBS buffer solution containing 150 μmol / L dopamine, with a pH of 7.0.
[0099] Example 10
[0100] Compared with Example 1, most of the steps are the same, except for step (5) in the preparation of the electrochemical sensor:
[0101] The electrolyte was a PBS buffer solution containing 150 μmol / L dopamine, with a pH of 8.0.
[0102] Embodiment 11
[0103] Compared with Example 1, most of the steps are the same, except for step (5) in the preparation of the electrochemical sensor:
[0104] The electrolyte was a PBS buffer solution containing 150 μmol / L dopamine, with a pH of 9.0.
[0105] Example 12
[0106] Compared with Example 1, most of the steps are the same, except for step (5) in the preparation of the electrochemical sensor:
[0107] The scan rate was 20 mV / s.
[0108] Embodiment 13
[0109] Compared with Example 1, most of the steps are the same, except for step (5) in the preparation of the electrochemical sensor:
[0110] The scan rate was 40 mV / s.
[0111] Embodiment 14
[0112] Compared with Example 1, most of the steps are the same, except for step (5) in the preparation of the electrochemical sensor:
[0113] The scan rate was 60 mV / s.
[0114] Embodiment 15
[0115] Compared with Example 1, most of the steps are the same, except for step (5) in the preparation of the electrochemical sensor:
[0116] The scan rate was 80 mV / s.
[0117] Example 16
[0118] Compared with Example 1, most of the steps are the same, except for step (5) in the preparation of the electrochemical sensor:
[0119] The scan rate was 120 mV / s.
[0120] Embodiment 17
[0121] Compared with Example 1, most of the steps are the same, except for step (5) in the preparation of the electrochemical sensor:
[0122] The scan rate was 140 mV / s.
[0123] Embodiment 18
[0124] Compared with Example 1, most of the steps are the same, except for step (5) in the preparation of the electrochemical sensor:
[0125] The scan rate was 160 mV / s.
[0126] Embodiment 19
[0127] Compared with Example 1, most of the steps are the same, except for step (5) in the preparation of the electrochemical sensor:
[0128] The scan rate was 180 mV / s.
[0129] Embodiment 20
[0130] Compared with Example 1, most of the steps are the same, except for step (5) in the preparation of the electrochemical sensor:
[0131] The scan rate was 200 mV / s.
[0132] Comparative Example 1
[0133] An electrochemical sensor based on a Co3O4@MXene composite material, compared with Example 1, does not add MXene, and its preparation process includes the following steps:
[0134] (1) Preparation of Co3O4
[0135] Weigh 0.291g of Co(NO3)2·6H2O and add 20ml of methanol, stir magnetically for 10min to obtain liquid A; weigh 0.328g of 2-methylimidazole and add 20ml of methanol, stir magnetically to obtain liquid B. Then pour liquid B into liquid A to mix, stir continuously for 24 hours at room temperature, centrifuge and wash with methanol at 6000rpm for 3 times, each centrifugation for 5min, and vacuum dry at 60℃ to obtain purple powder. The obtained purple powder is calcined at 400℃ for 2h in a muffle furnace and cooled naturally to obtain black Co3O4 nanoparticles.
[0136] (2) Preparation of rGO
[0137] Take 100 mg GO as raw material and 0.5 g ascorbic acid as reducing agent, and after ultrasonic homogenization to obtain a mixed solution, the mixed solution is transferred to a high-pressure reactor and reacted at 180 ° C for 12 hours in a homogeneous reactor. After cooling to room temperature, centrifuge at 5000 rpm for 5 minutes to obtain a solid, wash it with water and ethanol three times respectively, and dry it in a vacuum drying oven at 60 ° C overnight to obtain rGO.
[0138] (3) Preparation of Co3O4@rGO composites
[0139] A certain amount of rGO powder was ultrasonicated in purified water for 15 minutes to obtain a well-dispersed rGO solution. Then Co3O4 was added to make the mass ratio of Co3O4 nanoparticles to rGO 2:1, and ultrasonication was continued for 3 minutes. Centrifugation was performed at 6000 rpm for 5 minutes, and the centrifuged product was placed in a vacuum drying oven at 60°C for 24 hours to obtain Co3O4@rGO nanocomposite materials.
[0140] (5) Preparation of electrochemical sensors
[0141] The glassy carbon electrode (GCE) was polished to a mirror surface using 0.3 μm and 0.05 μm alumina powder on a polishing flannel, respectively, and ultrasonically cleaned several times with pure water and ethanol, respectively, and dried naturally. The GCE was activated using cyclic voltammetry (CV) in 0.5 mol / l H2SO4 solution with a scan rate of 0.1 V s -1 , the voltage range is -1 to 1V. After washing and drying, a clean and activated glassy carbon electrode is obtained and dried for later use.
[0142] 2.0 mg of Co3O4@rGO composite material was added to 1 ml of purified water, and 2 mg / ml of fully dispersed Co3O4@rGO composite material suspension was obtained by ultrasonic treatment. 5.0 μL of Co3O4@rGO composite material suspension was dropped on the pretreated GCE surface and dried in an oven at 37 °C to obtain the modified electrode Co3O4@rGO / GCE, which was used as the working electrode.
[0143] The electrochemical sensor uses a three-electrode system, with Co3O4@rGO / GCE as the working electrode, Ag / AgCl electrode as the reference electrode, and platinum wire electrode as the counter electrode. The electrochemical response of different modified electrodes to dopamine is detected by cyclic voltammetry. The electrolyte is a PBS buffer solution containing 150μmol / L dopamine, and the test potential range is 0V to 0.4V.
[0144] Comparative Example 2
[0145] An electrochemical sensor based on Co3O4@MXene composite material, compared with Example 1, does not add rGO, and its preparation process includes the following steps:
[0146] (1) Preparation of Co3O4
[0147] Weigh 0.291g of Co(NO3)2·6H2O and add 20ml of methanol, stir magnetically for 10min to obtain liquid A; weigh 0.328g of 2-methylimidazole and add 20ml of methanol, stir magnetically to obtain liquid B. Then pour liquid B into liquid A to mix, stir continuously for 24 hours at room temperature, centrifuge and wash with methanol at 6000rpm for 3 times, each centrifugation for 5min, and vacuum dry at 60℃ to obtain purple powder. The obtained purple powder is calcined at 400℃ for 2h in a muffle furnace and cooled naturally to obtain black Co3O4 nanoparticles.
[0148] (2) Preparation of MXene
[0149] Add 1.6g LiF to 20mL 9mol / L HCl solution and stir for 10 minutes to obtain an etching solution. Then gradually add 1g Ti3AlC2 powder to the above etching solution and stir at 45°C for 24 hours. Then wash the solid residue with deionized water and centrifuge several times until the pH value of the supernatant reaches 6. The collected solids are redispersed and ultrasonicated in an ice water bath and argon environment. After that, the dark green dispersion is centrifuged at 3000pm for 60min, and the upper liquid is collected and freeze-dried to obtain powdered MXene nanosheets, which are stored for later use.
[0150] (3) Preparation of Co3O4@MXene composites
[0151] A certain amount of MXene powder was ultrasonicated in purified water for 15 minutes to obtain a well-dispersed MXene solution. Then Co3O4 was added to make the mass ratio of Co3O4 nanoparticles to MXene 2:1, and ultrasonication was continued to be uniform, centrifuged at 5000 rpm for 5 minutes, and dried in a vacuum drying oven at 60°C for 24 hours to obtain Co3O4@MXene nanocomposite materials.
[0152] (5) Preparation of electrochemical sensors
[0153] The glassy carbon electrode (GCE) was polished to a mirror surface using 0.3 μm and 0.05 μm alumina powder on a polishing flannel, respectively, and ultrasonically cleaned several times with pure water and ethanol, respectively, and dried naturally. The GCE was activated using cyclic voltammetry (CV) in 0.5 mol / l H2SO4 solution with a scan rate of 0.1 V s -1 , the voltage range is -1 to 1V. After washing and drying, a clean and activated glassy carbon electrode is obtained and dried for later use.
[0154] 2.0 mg of Co3O4@MXene composite material was added to 1 ml of purified water, and 2 mg / ml of fully dispersed Co3O4@MXene composite material suspension was obtained by ultrasonic treatment. 5.0 μL of Co3O4@MXene composite material suspension was dropped on the pretreated GCE surface and dried in an oven at 37 °C to obtain the modified electrode Co3O4@MXene / GCE, which was used as the working electrode.
[0155] The electrochemical sensor uses a three-electrode system, with Co3O4@MXene / GCE as the working electrode, Ag / AgCl electrode as the reference electrode, and platinum wire electrode as the counter electrode. The electrochemical response of different modified electrodes to dopamine is detected by cyclic voltammetry. The electrolyte is a PBS buffer solution containing 150μmol / L dopamine, and the test potential range is 0V to 0.4V.
[0156] Comparative Example 3
[0157] A Co3O4-based electrochemical sensor, the preparation process of which includes the following steps:
[0158] (1) Preparation of Co3O4
[0159] Weigh 0.291g of Co(NO3)2·6H2O and add 20ml of methanol, stir magnetically for 10min to obtain liquid A; weigh 0.328g of 2-methylimidazole and add 20ml of methanol, stir magnetically to obtain liquid B. Then pour liquid B into liquid A to mix, stir continuously for 24 hours at room temperature, centrifuge and wash with methanol at 6000rpm for 3 times, each time for 5min, and vacuum dry at 60℃ to obtain purple powder. The obtained purple powder is calcined at 400℃ for 2h in a muffle furnace and cooled naturally to obtain black Co3O4 powder.
[0160] (2) Preparation of electrochemical sensors
[0161] The glassy carbon electrode (GCE) was polished to a mirror surface using 0.3 μm and 0.05 μm alumina powder on a polishing flannel, respectively, and ultrasonically cleaned several times with pure water and ethanol, respectively, and dried naturally. The GCE was activated using cyclic voltammetry (CV) in 0.5 mol / l H2SO4 solution with a scan rate of 0.1 V s -1 , the voltage range is -1 to 1V. After washing and drying, a clean and activated glassy carbon electrode is obtained and dried for later use.
[0162] 2.0 mg Co3O4 was added to 1 ml purified water and ultrasonicated to obtain a 2 mg / ml fully dispersed Co3O4 suspension. 5.0 μL of the Co3O4 suspension was dropped on the pretreated GCE surface and dried in an oven at 37°C to obtain the modified electrode Co3O4 / GCE, which was used as the working electrode.
[0163] The electrochemical sensor was obtained by using a three-electrode system with Co3O4 / GCE as the working electrode, Ag / AgCl electrode as the reference electrode, and platinum wire electrode as the counter electrode. The electrochemical response of different modified electrodes to dopamine was detected by cyclic voltammetry. The electrolyte was a PBS buffer solution containing 150 μmol / L dopamine, and the test potential range was 0V to 0.4V.
[0164] Figure 1 This is a morphology and structure characterization diagram of Co3O4, MXene, and Co3O4@MXene-rGO nanocomposites prepared in Example 1. Figure 1 a is Co3O4 derived from MOF calcination. It can be seen that Co3O4 maintains a perfect cubic structure with a particle size of about 150-200nm. In addition, due to the decomposition and release of organic ligands during the calcination process, Co3O4 has an obvious porous structure, which is beneficial to increase the specific surface area of the material, but there is agglomeration. Figure 1 b is the TEM image of MXene, which shows an obvious two-dimensional lamellar structure. Figure 1 c is the SEM image of Co3O4@MXene-rGO nanocomposite. Metal oxide Co3O4 nanoparticles are evenly distributed on the surface of three-dimensional MXene-rGO aerogel, exposing more active sites and greatly promoting electron transfer. Figure 1 d High-resolution transmission electron microscopy (HRTEM) image can further clarify the crystal structure of the composite material.
[0165] Figure 2 This is the XRD diagram of the Co3O4@MXene-rGO nanocomposite prepared in Example 1. It can be seen that all the diffraction peaks of Co3O4 perfectly match the cubic phase Co3O4 standard JCPDS NO.42-1467. The diffraction peaks of Co3O4, MXene and rGO are clearly present in the XRD of the composite material, indicating that the composite material was successfully prepared.
[0166] Figure 3The CV curves of dopamine obtained by different working electrodes in Example 1 and Comparative Examples 1 to 4 show that the CV curves of all electrodes show a pair of clear redox peaks, corresponding to the redox reaction of dopamine. The electrochemical responses of GCE and Co3O4 / GCE are very weak, while Co3O4@rGO / GCE, Co3O4@MXene / GCE and Co3O4@MXene-rGO / GCE all show significant electrochemical responses to dopamine, among which Co3O4@MXene-rGO / GCE observes the strongest current signal, indicating that the Co3O4@MXene-rGO composite material provides more active sites, enhances the electron conduction ability, and plays a significant electrocatalytic role in the redox reaction of dopamine.
[0167] The effect of the amount of Co3O4@MXene-rGO composite suspension drop on the electrochemical signal was investigated. Examples 1, 3 to 7 were drop-coated on the GCE surface at 14.1 μL / cm 2 , 42.4μL / cm 2 、70.7μL / cm 2 , 99.0μL / cm 2 , 127.3μL / cm 2 of Co3O4@MXene-rGO composite suspension (2 mg / ml) and then electrochemical detection was performed. Figure 4 The DPV test results of 150μM dopamine solution with different droplet volumes are shown in Figure 1. The results show that the DPV of 150μM dopamine solution is 14.1-70.7μL / cm 2 As the drop volume increases, the current response signal increases, because the added composite material provides more reactive sites for dopamine. However, if the drop volume continues to increase, the current response gradually decreases, because too much modified material hinders the transfer of electrons and affects the current signal. Therefore, 70.7 μL / cm 2 For the best drop amount.
[0168] The effect of different pH values of the buffer solution on the electrochemical signal was explored. The pH of the buffer solution will have a significant impact on the electrochemical reaction of dopamine, so the pH of the PBS buffer solution was optimized. Figure 5 a It can be seen that the oxidation peak current of dopamine on the modified electrode increases first and then decreases, and the peak current value is the largest when pH = 6.2. Therefore, the optimal pH of the PBS buffer solution selected by the present invention is 6.2. Figure 5 In b, as the pH increases, the oxidation peak potential of dopamine on the Co3O4@MXene-rGO modified electrode shifts negatively, indicating that protons participate in the redox reaction. Calculations show that the oxidation peak potential of dopamine has a good linear relationship with pH. The linear regression equation is: Epa = -0.054pH + 0.5428 (R2 =0.9981). This indicates that the reaction of dopamine on the surface of Co3O4@MXene-rGO / GCE is an “iso-electron-iso-proton” transfer process.
[0169] The effect of scan rate on electrochemical signals was investigated. Cyclic voltammetry was used to record the changes in the redox peaks of dopamine on Co3O4@MXene-rGO / GCE at scan rates of 20 to 200 mV / s. Figure 6 The results show that as the scan rate increases, the oxidation peak current Ipa and reduction peak current Ipc of dopamine increase, and show a good linear relationship ( Figure 6 b), the linear regression equations are: pa =0.4021υ+1.1447(R 2 =0.9922), I pc =-0.3264υ-8.394(R 2 =0.9934). The above results indicate that the redox process of dopamine on Co3O4@MXene-rGO / GCE is an adsorption-controlled process. Low scan rate results in small current response and poor sensitivity. Conversely, as the scan rate increases, the current response increases, but the reversibility of the redox reaction deteriorates. Therefore, the optimal scan rate selected in this experiment is 100mV·s -1 .
[0170] The electrochemical sensor and electrochemical signal detection parameters in Example 1 were used to explore the relationship between the oxidation peak current and the dopamine concentration. (Drop volume 70.7 μL / cm 2 The DPV method was used to study the quantitative analysis of dopamine at different concentrations of Co3O4@MXene-rGO / GCE under the conditions of 40 ℃, pH 6.2, and scan rate 100 mV / s. Figure 7 As shown in a, within the range of 1 to 300 μM, the oxidation peak current increases with the increase of dopamine concentration, showing a good positive correlation ( Figure 7 b), the linear regression equation is I(μA)=0.6215C DA +8.5720(R 2 =0.998). At a signal-to-noise ratio (S / N) of 3 times, the limit of detection (LOD) is 0.04 μM. Compared with other nanomaterial-modified electrodes introduced in the literature in recent years (see Table 1 below), the Co3O4@MXene-rGO / GCE sensor constructed in this experiment shows a wider detection range and a lower detection limit.
[0171] Table 1 Comparison of electrochemical sensor performance obtained by electrodes modified with different nanomaterials
[0172]
[0173] Note:
[0174] Literature [1]: Y. Wang, D. Ren, Y. Zhang, J. Li, W. Meng, B. Tong a, J. Zhang, C. Han, L. Dai, Insitu integrated electrodes of FeM-MIL-88 / CP for simultaneous ultra-sensitive detection of dopamine and acetaminophen based on crystalengineering strategy, Anal. Chim. Acta 1283 (2023) 341936.
[0175] Literature [2]: Y. Xue, H. Li, X. Wang, X. Xuan, M. Li, Preparation of self-supportingvertically / horizontally grown graphene microelectrodes for neurotransmitterdetermination, Anal. Chim. Acta 1269 (2023) 341414.
[0176] Literature [3]: L. Zhang, J. Guo, M. Yuan, Y. Xu, Z. Pu, C. Tan, Q. Wang, X. Xiong, Microplasma-induced in situ rapid synthesis of CoSe nanosphere@N-dopedpolymeric carbon dots derived from ZIF-67for highly sensitive dopaminedetection, Anal Chim Acta 1329 (2024) 343236.
[0177] Literature [4]: E. Bahrami, R. Amini, S. Vardak, Electrochemical detection ofdopamine via pencil graphite electrodes modified by Cu / CuxO nanoparticles, J.Alloy. Compd. 855 (2021), 157292.
[0178] Reference [5]: C. Chen, J. Ren, P. Zhao, J. Zhang, Y. Hu, J. Fei, A novel dopamine electrochemical sensor based on a β-cyclodextrin / Ni-MOF / glassy carbon electrode, Microchem. J. 194 (2023) 109328.
[0179] Reference [6: L. Xu, C. Ling, L. Ou, Y. Jin, C. Tan, Y. Gao, X. Xiong, Mo-doped CoP nanoparticles embedded bamboo-like N-doped carbon nanotube modified hollow carbon nanocage for electrochemical sensing of dopamine in human serum and meat samples, Food chemistry 464 (2024) 141847.
[0180] Reference [7]: K. Zhou, D. Shen, X. Li, Y. Chen, L. Hou, Y. Zhang, J. Sha, Molybdenum oxide-based metal-organic framework / polypyrrole nanocomposites for enhancing electrochemical detection of dopamine, Talanta 209 (2020) 120507.
[0181] Reference [8]: C. Lu, Y. Ma, W. Zhu, Y. Cao, Y. Cao, Q. Huang, X. Wang, J. Wang, Cu / Cu2O / CuO catalyst generated by disproportionation for electrochemical dopamine sensing with improved stability and sensitivity, Microchemical Journal 193 (2023) 108966.
[0182] Literature [9]: Y.Ma,
[0183] Literature
[10] : Y. Hou, K. Sheng, Y. Lu, C. Ma, W. Liu, X. Men, L. Xu, S. Yin, B. Dong,
[0184] Using the electrochemical sensor and electrochemical signal detection parameters in Example 1, DPV was used to measure 100 times the concentration of MgCl, KCl, NaCl, Na2CO3, urea, glucose, ascorbic acid, glycine, and proline added to 10 μM dopamine. The results show that these interferents have no obvious effect on the detection of dopamine, indicating that the selectivity of the electrochemical sensor obtained by Co3O4@MXene-rGO / GCE for dopamine detection is satisfactory. Under the same conditions, five electrochemical sensors with Co3O4@MXene-rGO / GCE as working electrodes were constructed, and the same concentration of dopamine was detected to evaluate the reproducibility of the electrode. The relative standard deviation of the oxidation peak current of the five electrodes was obtained to be 2.1%, indicating that the electrochemical sensor constructed by Co3O4@MXene-rGO / GCE has good reproducibility. Co3O4@MXene-rGO / GCE was stored at 4°C, and its current response to the same concentration of dopamine was studied for 7 consecutive days. The results showed that the current did not change much with the extension of storage time, and the peak current measured on the seventh day was 95.75% of the initial current, indicating that the constructed electrochemical sensor had excellent stability.
[0185] In order to verify the accuracy of the electrochemical sensor obtained in the present invention for quantitative detection of dopamine, under the experimental conditions of Example 1, the electrochemical sensor constructed in Example 1 with Co3O4@MXene-rGO / GCE as the working electrode was used to detect the spiked recovery rate of dopamine in human serum samples. The measured recovery rate ranged from 95.27% to 103.65%, indicating that the electrochemical sensor proposed in the present invention can be accurately and reliably used for the analysis of dopamine in actual samples.
[0186] Although the present invention has been described in detail above by means of general description, specific implementation methods and tests, it is obvious to those skilled in the art that some modifications or improvements may be made to the present invention. Therefore, these modifications or improvements made without departing from the spirit of the present invention all fall within the scope of protection claimed by the present invention.
Claims
1. An electrochemical sensor based on Co3O4@MXene-rGO composite material, characterized in that: The electrochemical sensor comprises a working electrode, a counter electrode and a reference electrode, and the surface of the working electrode is modified with a Co3O4@MXene-rGO nanocomposite material.
2. An electrochemical sensor based on Co3O4@MXene-rGO composite material according to claim 1, characterized in that: The Co3O4@MXene-rGO nanocomposite material comprises Co3O4 nanoparticles and MXene-rGO composite aerogel, and the Co3O4 nanoparticles are uniformly distributed on the surface of the MXene-rGO composite aerogel.
3. An electrochemical sensor based on Co3O4@MXene-rGO composite material according to claim 1, characterized in that: The preparation method of the Co3O4@MXene-rGO nanocomposite material is as follows: Co3O4 nanoparticles are mixed with MXene-rGO composite aerogels, and the Co3O4@MXene-rGO nanocomposite material is obtained by ultrasonication, centrifugation, washing and drying.
4. An electrochemical sensor based on Co3O4@MXene-rGO composite material according to claim 3, characterized in that: The mass ratio of the Co3O4 nanoparticles to the MXene-rGO composite aerogel is 1 to 3:
1.
5. An electrochemical sensor based on Co3O4@MXene-rGO composite material according to claim 3, characterized in that: The Co3O4 nanoparticles are derived from MOF, and the preparation process of the Co3O4 nanoparticles is as follows: a cobalt source and 2-methylimidazole are dissolved in methanol respectively, mixed, centrifuged, and dried to obtain a cobalt-based MOF, and calcined to obtain the Co3O4 nanoparticles; The preparation process of the MXene-rGO composite aerogel is as follows: MXene and rGO are ultrasonically treated and then freeze-dried to obtain the MXene-rGO composite aerogel.
6. An electrochemical sensor based on Co3O4@MXene-rGO composite material according to claim 5, characterized in that: In the preparation process of the Co3O4 nanoparticles: The molar ratio of the cobalt source to 2-methylimidazole is 1:4-12. The cobalt source includes cobalt nitrate, cobalt chloride, and cobalt acetate. The calcination temperature is 300-600°C; During the preparation of the MXene-rGO composite aerogel: The mass ratio of MXene to rGO is 1:0.5-2. The MXene includes Ti3C2 MXene, Ti2C MXene, Nb2C MXene, V2C MXene, The rGO is obtained by reducing GO.
7. An electrochemical sensor based on Co3O4@MXene-rGO composite material according to claim 1, characterized in that: The working electrode is a glassy carbon electrode or a screen-printed electrode whose surface is modified with Co3O4@MXene-rGO nanocomposite material; The counter electrode includes a platinum wire electrode, a platinum sheet electrode, and a graphite electrode; The reference electrode includes an Ag / AgCl electrode and a calomel electrode.
8. A method for preparing an electrochemical sensor based on a Co3O4@MXene-rGO composite material according to any one of claims 1 to 7, characterized in that: The Co3O4@MXene-rGO nanocomposite material is dispersed in a solvent to obtain a Co3O4@MXene-rGO nanocomposite material suspension, which is drop-coated on the surface of a working electrode, and after drying, it is assembled with a reference electrode and a counter electrode to obtain an electrochemical sensor.
9. The method for preparing an electrochemical sensor based on a Co3O4@MXene-rGO composite material according to claim 8, characterized in that: The drop coating amount of the Co3O4@MXene-rGO nanocomposite suspension is 10-150 μL / cm 2 ; The concentration of the Co3O4@MXene-rGO nanocomposite in the Co3O4@MXene-rGO nanocomposite suspension is 1 to 5 mg / mL; The solvent includes water and ethanol.
10. The use of an electrochemical sensor based on a Co3O4@MXene-rGO composite material according to any one of claims 1 to 7, characterized in that: Applied to the detection of dopamine.
Citation Information
Patent Citations
Dopamine detection electrochemical sensor based on nano-porous MXene material
CN118191061A
Cited By
Multi-channel electrochemical sensor and preparation method thereof
CN120721815A